The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1017/pds.2022.11
|View full text |Cite
|
Sign up to set email alerts
|

Co-Designing with AI in Sight

Abstract: Artificial Intelligence offers a wide variety of capabilities that can potentially address people's needs and desires in their specific contexts. This pilot study presents a collaborative method using a deck of AI cards tested with 58 production, AI, and information science students, and experts from an accessible media agency. The results suggest that, with the support of the method and AI cards, participants can ideate and reach conceptual AI solutions. Such conceptualisations can contribute to a more inclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Additionally, our research team has continued to delve into PSS approaches in healthcare that exploit AI. Our findings have shown that there is research being done in the filed of AI in rehabilitation (Davenport and Kalakota, 2019;Neuhüttler et al, 2020;Preidel and Stark, 2021;Aranda-Muñoz et al, 2022;Mennella et al, 2023) and AI in prosthetics and orthotics (Mai and Commuri, 2013;Kidziński et al, 2019;Nayak and Kumar Das, 2020;. To date, no explicit PSS literature (with or without the use of AI) concerning amputee aftercare, their evolving needs or the manufacture, distribution, ownership and use of prosthetics has been found.…”
Section: State Of the Art Product Service Systems For Amputee Healthcarementioning
confidence: 66%
“…Additionally, our research team has continued to delve into PSS approaches in healthcare that exploit AI. Our findings have shown that there is research being done in the filed of AI in rehabilitation (Davenport and Kalakota, 2019;Neuhüttler et al, 2020;Preidel and Stark, 2021;Aranda-Muñoz et al, 2022;Mennella et al, 2023) and AI in prosthetics and orthotics (Mai and Commuri, 2013;Kidziński et al, 2019;Nayak and Kumar Das, 2020;. To date, no explicit PSS literature (with or without the use of AI) concerning amputee aftercare, their evolving needs or the manufacture, distribution, ownership and use of prosthetics has been found.…”
Section: State Of the Art Product Service Systems For Amputee Healthcarementioning
confidence: 66%
“…AI use will broadly affect a wide range of business areas and functions (van Giffen et al, 2020). Initial approaches involving individuals without broad AI expertise in the development of AI applications use AI Cards as an ad hoc means of mitigating the lack of knowledge (Aranda-Muñoz et al, 2022). The lack of detailed standardised models of AI development makes it difficult to communicate with non-IT engineers.…”
Section: Iced23mentioning
confidence: 99%
“…Also, of great importance is domain knowledge to be able to identify the potential of applications and use cases, and thus initiate bottom-up AI projects. People without much IT expertise should also be involved in the systematic processes to identify application opportunities (Aranda-Muñoz et al, 2022). At this point, care must be taken not to create a missing link between top-down and bottom-up perspectives in scientific literature.…”
Section: Iced23mentioning
confidence: 99%
“…Hence, the ML software is a material, which can act as instruments of inquiry to support designers in ideating and exploring in the design space . Thus, when designing with ML software, the designer sees what the software produces, adjusts and re-prompts the software and then evaluates the outcome (Aranda-Muñoz et al, 2022) iteratively to develop a design.…”
Section: Reflective Practice With ML Softwarementioning
confidence: 99%